Aproveitamento de resíduos alimentares para geração de produto gourmetizado - Pereira, Juliano Sebastião Gonçalves (2018)
According to the report of the Food and Agriculture Organization of the United Nations (FAO), there is an alarming food waste in the world, causing significant damage to society, and leading to economic losses and damage to the environment. However, these losses may be reduced by combining concepts of sustainability and gastronomy. Based on this premise, this study aimed to investigate the technical, microbiological and sensorial feasibility for the use of fruits, with an advanced degree of ripening and/or with few physical damages, in gastronomic preparation sophisticated and safe for human consumption. A product named guava chutney was developed and later used in a gastronomic preparation called Finger Food, traditionally served in highgastronomy restaurants. For the development of this product, three treatments of chutney were established, as follow: T1, using exclusively red guavas (Psidium guajava) and apples (Malus domestica) in perfect conditions of sale for consumers; T2, using exclusively guavas and apples damaged and/or with a high degree of ripening; and T3, using guavas, apples, and tomatoes (Solanum lycopersicum), also in conditions of damage and/or with high degree of ripening. Finger food was characterized as a gastronomic composition composed of natural fermentation bread, chutney, pulled sun-dried meat and chives (Allium schoenoprasum) as a decoration element. Three types of finger food were made, respectively according to the previously developed chutney preparations. The research was quali-quantitative, divided into nine stages: ethical approval, critical observation, pre-experiment, chutney and finger food development and preparation, chemical analysis, microbiological analysis, semi-structured interviews, sensorial tests, and data statistical analysis. All elaborated chutney treatments showed low microbiological counts of coliforms (<1 MPN.g-1), molds and yeasts (<1 CFU.g-1), proving to be safe for consumption. Regarding the sensorial analysis, they had a good global acceptance (from 7.3 to 7.6 points for chutney and from 7.0 to 7.4 points for finger food, showing no significant difference between the samples) and good intention of consumption (3.6 to 39 points for both chutney and finger food, with no significant difference between the samples). Most of the interviewed people adopt habits in an attempt to minimize waste (69.3%) and showed a trend in consuming products made from wasted food (84.1%). From the data, we concluded it is possible to combine concepts of sustainability and gastronomy, associated with Experimental Marketing and High Low, to turn a food, that would not normally be consumed, into a “gourmetized” gastronomic preparation with added value and high sensory acceptance rate, making possible a reduction of losses in the food chain.